Wide absorption bandwidth of a light composite absorber based on micro-perforated sandwich panel. (March 2021) - Ning, Jingfeng; Geng, Qian; MP, Arunkumar; Li, Yueming
Abstract: We present a light composite absorber consisting of a micro-perforated sandwich panel (MSP) filled with a thin porous materials, to achieve a wide absorption bandwidth. The MSP is of 1 mm thickness scale and possesses the excellent mechanic properties in contrast to a single homogeneous panel. The theoretical model of the light composite absorber is derived by the transfer matrix method, and is well agreed with the experimental results. The proposed absorber predicts a wider 0.5 relative absorption bandwidth and higher absorption coefficient, compared with the micro-perforated panel (MPP) absorber or the double-MPPs absorber. The absorption mechanism owing to the addition of the thin porous materials is conducted by analyzing the reflection coefficient, surface acoustic impedance, acoustic pressure and local velocity. The influences of the thickness, porosity, and hole diameter of the internal components on the absorption bandwidth and absorption peak are discussed. The proposed absorber has a wide scope of potential applications under multi-functional noise-controlled conditions